2015
DOI: 10.2131/jts.40.329
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-let-7g miRNA regulates the anti-tumor effects of gastric cancer cells under oxidative stress through the expression of DDR genes

Abstract: -Oxidative stress is linked to increased risk of gastric cancer (GC). Recent reports have found that hsa-let-7g microRNA (miRNA) has properties of anti-tumor and resistance to damages induced by oxidized low-density lipoprotein (ox-LDL). Dysregulation of hsa-let-7g was present in GC in vivo and in vitro under exogenous stress. However, we didn't know whether there are regulatory mechanisms of hsa-let-7g in GC under oxidative stress. This study was aimed at investigating the effects of hsa-let-7g microRNA (miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The Let-7 family has 10 members in the human genome (Let-7a, let-7b, let-7c, let-7d, let-7e, let-7f, let-7g, let-7i, miR-98, and miR-202 38 ), which are involved in gene regulation and cell adhesion. We found, Let-7f microRNAs were strikingly downregulated in HGDN and eHCC (1 million-fold change) and Let-7g in HCC (358-fold change) with similar reports published in gastric 39 , 40 , prostate 41 , colon 42 , 43 , small cell lung 44 , thyroid 45 , breast 46 , 47 , and hepatocellular cancer 48 , 49 . miR-221, was found to be upregulated in HCC via in silico analysis and has multiple known pathway targets, such as p27Kip1, p53, BMF, PI3K, PTEN, and mTOR 50 .…”
Section: Discussionsupporting
confidence: 89%
“…The Let-7 family has 10 members in the human genome (Let-7a, let-7b, let-7c, let-7d, let-7e, let-7f, let-7g, let-7i, miR-98, and miR-202 38 ), which are involved in gene regulation and cell adhesion. We found, Let-7f microRNAs were strikingly downregulated in HGDN and eHCC (1 million-fold change) and Let-7g in HCC (358-fold change) with similar reports published in gastric 39 , 40 , prostate 41 , colon 42 , 43 , small cell lung 44 , thyroid 45 , breast 46 , 47 , and hepatocellular cancer 48 , 49 . miR-221, was found to be upregulated in HCC via in silico analysis and has multiple known pathway targets, such as p27Kip1, p53, BMF, PI3K, PTEN, and mTOR 50 .…”
Section: Discussionsupporting
confidence: 89%
“…11 The hsa-let-7g miRNA (also known as miR-let-7g and let-7g) is a member of the let-7 miRNA family that can exert vital biological effects in various diseases, including cancer. Hu, et al 12 reported that hsa-let-7g can exert anti-tumor effects in gastric cancer by inhibiting oncogenesis induced by oxidative stress. Another study indicated that hsa-let-7g could serve as an indicator for the prognosis of S-1-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] In gastric cancer cells, let-7g was reported to induce sensitivity to oxidative stress by indirect repression of DNA damage responsive and served as a tumor suppressor gene. [ 26 ] In breast cancer tissues and cell lines, low expression of let-7g was associated with invasion and metastasis, further supporting its role as a tumor suppressor gene. [ 27 ] MiR-143 levels have been reported to be lower in bladder cancer tissue than normal tissue.…”
Section: Discussionmentioning
confidence: 99%